Raman Spectroscopy as a Robust New Tool for Rapid and Accurate Evaluation of Drought Tolerance Levels in Both Genetically Diverse and Near-Isogenic Maize Lines - Altangerel, Narangerel; Huang, Pei-Cheng; Kolomiets, Michael V.; Scully, Marlan O.; Hemmer, Philip R. (Frontiers in Plant Science, 2021)
Improving drought tolerance of crops has become crucial due to the current scenario of rapid climate change. In particular, development of new maize germplasm with increased drought tolerance is viewed as a major breeding goal to ensure sustainable food and feed production. Therefore, accurate rapid phenotyping techniques for selection of superior maize genotypes are required. The objectives of this study were to determine whether Raman microscopy technique can be applied for accurate assessment of drought-tolerance levels in both genetically diverse and near-isogenic maize lines that differ in their levels of drought-tolerance. Carotenoid degradation is known to be a direct stress response initiated by reactive oxygen species during osmotic stress such as drought. Using Raman mapping, we observed real-time changes in the rate of carotenoid degradation in chloroplasts that was dependent on the strength of osmotic stress. In addition, we showed that the rate of carotenoid degradation as measured by Raman spectroscopy correlates directly with drought tolerance levels of diverse maize genotypes. We conclude that Raman technique is a robust, biochemically selective and non-invasive phenotyping technique that accurately distinguishes drought tolerance levels in both genetically diverse and near-isogenic maize genotypes. We conclude that this technique can be further developed to render it suitable for field-based early assessment of breeding materials with superior drought-tolerance traits.